3D Microfabricated Scaffolds: A 3D Microfabricated Scaffold System for Unidirectional Cell Migration (Adv. Biosys. 10/2020). Issue 10 (16th October 2020) - Sunami, Hiroshi; Shimizu, Yusuke; Denda, Junko; Yokota, Ikuko; Kishimoto, Hidehiro; Igarashi, Yasuyuki
Abstract : In article number 2000113, Hiroshi Sunami and co‐workers demonstrate unidirectional cell migration using a novel three‐dimensional microfabricated scaffold. The three‐dimensional scaffolds could provoke cells to accumulate in a single target location or could provoke dissipated cell distribution. Because the shapes are very simple, the scaffolds could be applied to the surfaces of various medical devices.